2007
DOI: 10.1016/j.taap.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Transport of thiol-conjugates of inorganic mercury in human retinal pigment epithelial cells

Abstract: Inorganic mercury (Hg 2+ ) is a prevalent environmental contaminant to which exposure to can damage rod photoreceptor cells and compromise scotopic vision. The retinal pigment epithelium (RPE) likely plays a role in the ocular toxicity associated with Hg 2+ exposure in that it mediates transport of substances to the photoreceptor cells. In order for Hg 2+ to access photoreceptor cells, it must be first be taken up by the RPE, possibly by mechanisms involving transporters of essential nutrients. In other epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
0
24
1
3
Order By: Relevance
“…The visual field test is an indispensable diagnostic tool for glaucoma and optic nerve disease. It can also be used in the diagnosis of drug intoxications (Bridges et al, 2007;Herba et al, 2004;da Costa et al, 2008).. However, the test is subjective and the test results may be affected due to patient compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual field test is an indispensable diagnostic tool for glaucoma and optic nerve disease. It can also be used in the diagnosis of drug intoxications (Bridges et al, 2007;Herba et al, 2004;da Costa et al, 2008).. However, the test is subjective and the test results may be affected due to patient compliance.…”
Section: Discussionmentioning
confidence: 99%
“…It accumulates and leads to local or systemic action in the vitreous (Bridges et al, 2007;Tanan et al, 2006). The ionic mercury, carried in the blood to the retina pigment epithelium, is distributed into photoreceptors, plexiform layer, and ganglion cells (Beuter and Edwards, 2004;Bridges et al, 2007;Toimela and Tähti, 2001;Warfvinge and Bruun, 2000). Since the earliest affected cells are scotopic cells, decreased night vision may be seen as the first clinical sign.…”
Section: Introductionmentioning
confidence: 99%
“…Hg is a toxic and hazardous metal that may exist in the environment [180,181]. Exposure to mercurial compounds induces hepatotoxicity associated with oxidative stress [182][183][184][185], generating hepatocellular defects like hepatomegaly, centrilobular hepatic steatosis [186,187], decrease in the synthesis of hepatic coagulation factors [188][189][190][191][192] and diminution in the activity of metabolic enzymes [193].…”
Section: Mercury (Hg)mentioning
confidence: 99%
“…Large populations are currently exposed to low levels of Hg owing to the use of Hg pesticides in agriculture or as components of batteries in fluorescent light bulbs. Exposure of certain organs to Hg can result in serious toxicological consequences [1,2]. Previous studies [3,4] revealed that mercuric chloride (HgCl 2 ) can lead to tubule necrosis in the kidney.…”
Section: Introductionmentioning
confidence: 99%